THE ROLE OF THE MONTH OF BIOLOGICAL SCIENCES IN GENERAL EDUCATION INSTITUTIONS (Conference Zone, 2022)
This article discusses the importance of conducting the Month of Biological Sciences for improving the quality and effectiveness of education and creating the basis for high success.